La primera : the story of wild mustangs - Tyson, Ian, 1933-; Halvorson, Adeline (Toronto, Ont. ; Plattsburgh, N.Y. : Tundra Books, 2009)
Full-color illustrations and simple text trace the history of wild mustangs in North America, believed to have been introduced to the continent by Spanish conquistadors.
Resource Links
School Library Journal
3.9
K-3.
K-3
Keywords: Children's poetry, Canadian; Mustang -- Juvenile poetry; Canadian poetry; Mustangs -- Poetry; Canadian poetry; Mustangs -- Poetry